2020
DOI: 10.21608/ejh.2020.31508.1304
|View full text |Cite
|
Sign up to set email alerts
|

High-fructose diet induces earlier and more severe kidney damage than high-fat diet on rats

Abstract: Background: Several previous studies explored the toxic effect of high-fat diet (HFD) and high-fructose diet (HFrD), however little is known regarding their differential detrimental effects on the kidney. Aim: This study was conducted to compare the biochemical, histological, and molecular changes in the kidney induced by consumption of HFD and HFrD for 4 and 8 weeks. Materials and Methods: Thirty-five rats were randomly divided into five groups (n = 7/group): control, HFD1 (fed HFD for 4w), HFrD1 (for 4w), HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…High fructose solution was implemented in this study in order to induce renal damage due to its high expression of fructokinase (Diggle et al, 2009). A high-fructose diet causes renal morphological alteration through an increase in alpha-smooth muscle actin (α-SMA), inflammation, glomerulosclerosis, and necrosis gene expressions, leading to a reduction in the glomerular filtration rate (GFR) and higher urea and creatinine levels in the blood (Elsisy, El-Magd, & Abdelkarim, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…High fructose solution was implemented in this study in order to induce renal damage due to its high expression of fructokinase (Diggle et al, 2009). A high-fructose diet causes renal morphological alteration through an increase in alpha-smooth muscle actin (α-SMA), inflammation, glomerulosclerosis, and necrosis gene expressions, leading to a reduction in the glomerular filtration rate (GFR) and higher urea and creatinine levels in the blood (Elsisy, El-Magd, & Abdelkarim, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We also found an unusually large amount of adipose tissue in class B luncheon. Although fat plays a crucial role in the processed meat's organoleptic qualities and the goods' longevity, high consumption of meat products containing high fat content might be a major risk factor for obesity and being overweight [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that this type of diet can damage kidney structure, increase the expression of alpha-smooth muscle actin (αSMA), as well as genes related to inflammation and glomerulosclerosis, such as tumor necrosis alpha (TNF-α), interleukin 1β (IL-1β), nuclear factor kappa B (NF-κB), poly(ADP-ribose) polymerase-1 (PARP1), and receptor-interacting protein (RIP1). 6 This damage occurs due to an increase of superoxide anions caused by endothelial dysfunction, activation of the renin-angiotensin-aldosterone system, lipotoxicity, and adipokine imbalance. 4 Excessive superoxide anion levels suppress the activity of the superoxide dismutase (SOD) enzyme.…”
Section: Introductionmentioning
confidence: 99%